2021
DOI: 10.1177/03611981211017133
|View full text |Cite
|
Sign up to set email alerts
|

How Do Shared Dockless E-Scooter Services Affect Mobility Practices in Paris? A Survey-Based Estimation of Modal Shift

Abstract: Shared dockless e-scooters were first launched in Paris in the summer of 2018. These services were met with mixed reception: although some praised them for offering a new mobility solution to urban dwellers, others soon questioned their environmental impact. An emerging body of literature using lifecycle analysis shows that shared e-scooters are more pollutant than walking, cycling, and public transportation, but remain preferable to cars. To better grasp the impacts of dockless e-scooters, it is therefore nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…For example, in Paris (France), the results obtained from two surveys indicate that for their last trip riding a shared e-scooter, for most users who would have walked or used public transportation, e-scooters had not been an option: 44.4% for walking and 31.4% for public transportation in the first survey and 37.2% for walking and 35.9% for public transportation in the second survey [39]. In another study, also conducted in Paris, Christoforou et al found that 72% of users' movements by walking and public transport were replaced by a shared e-scooter, then 16% of those who used a motorized mode (private car, taxi, motorcycle) replaced the e-scooter, while very few would increase their mobility with new trips (6%) [40].…”
Section: How Does the E-scooter Influence The Change In The Modal Shift?mentioning
confidence: 99%
“…For example, in Paris (France), the results obtained from two surveys indicate that for their last trip riding a shared e-scooter, for most users who would have walked or used public transportation, e-scooters had not been an option: 44.4% for walking and 31.4% for public transportation in the first survey and 37.2% for walking and 35.9% for public transportation in the second survey [39]. In another study, also conducted in Paris, Christoforou et al found that 72% of users' movements by walking and public transport were replaced by a shared e-scooter, then 16% of those who used a motorized mode (private car, taxi, motorcycle) replaced the e-scooter, while very few would increase their mobility with new trips (6%) [40].…”
Section: How Does the E-scooter Influence The Change In The Modal Shift?mentioning
confidence: 99%
“…In Braga, shared e-scooters have a high possibility of replacing walking trips, although car users and public transport users would hold to their current mode of transport. This indicates that shared e-scooters have a higher potential to replace walking than car trips or public transport trips [49].…”
Section: Discussionmentioning
confidence: 99%
“…2.1 E-scooters Gössling (2020) dates shared e-scooters systems to 2017 in Los Angeles and points to a rapid growth in provision globally since then, comparable to that of public bike sharing (Spinney, 2020), another element of shared micromobility (Shaheen et al, 2020). With the rise in popularity of e-scooters there has been a growing body of research into their use, potential application and impact on cities and on mobility systems and practices (Caspi, Smart and Noland, 2020;Krier et al, 2021), examining how e-scooters might fit within and contribute to broader transport systems (Gössling, 2020;Rose et al, 2020) and how they are being used in, for example, Paris (Christoforou et al, 2021), Chicago (Mehzabin Tuli, Mitra and Crews, 2021), Munich and other German cities (Hardt and Bogenberger, 2019;König et al, 2022), Brisbane (Haworth, Schramm and Twisk, 2021), and Greater Manchester (Sherriff, Blazejewski and Lomas, 2022). Here we provide an overview of literature on their environmental impact, health implications, and challenges involved in sharing space with other road users.…”
Section: Contextmentioning
confidence: 99%